ANALISIS PENYELESAIAN SENGKETA NASABAH WANPRESTASI PERBANKAN DI PENGADILAN NEGERI KOLAKA - Evi Febryani (Jurnal Ekonomi Bisnis Syariah, 2020)
The Kolaka District Court is a judicial institution within the General Court which is located in Kolaka Regency.As a First Level Court, the Kolaka District Court functions to examine, decide, and settle criminal and civilcases for people who seek justice in general.The purpose of this study is to determine the process of settlementof customer disputes in default in the district court and to find out the judges' considerations in making decisionsregarding default disputes.The research method used is a qualitative approach and this type of research isdescriptive. The data and information collection methods used in this study were observation, in-depthinterviews, and documentation study. The data collected will be analyzed through 3 stages, namely reducingdata, presenting data, concluding and verifying data.The result of the research shows that the process of disputesettlement by customers of bank defaults in the District Court goes through the stages, namely the aggrievedparty submits a lawsuit for default and after being registered with CTS, the Chief Justice sets the Assembly.Then the Assembly determines the day of the trial and summons the parties through the Bailiff / SubstituteBailiff. Then mediation is carried out. However, if the mediation effort is unsuccessful, the next stage is toproceed in trial which includes reading of the lawsuit, the defendant's answers, replications, duplicates,evidence, conclusions, and up to the final stage, namely the verdict of the Panel of Judges. The Judge'sconsideration in giving decisions related to default disputes, namely where the consideration is taken based onthe evidence submitted by the plaintiff and defendant. The evidence is presented to strengthen the reasons foreach party.